Using Xpert MTB/RIF - P. Nicol, Mark; Whitelaw, Andrew; Stevens, Wendy (Current Respiratory Medicine Reviews, 2013)
Xpert MTB/RIF is an automated real-time polymerase chain reaction test for simultaneous detection of tuberculosis and rifampicin resistance. Xpert MTB/RIF has demonstrated excellent accuracy in clinical evaluation studies, but has reduced sensitivity for detection of smear-negative tuberculosis. Since sample processing and detection are largely automated, Xpert MTB/RIF is potentially suitable for implementation in resource-limited settings. There are, however, a number of practical constraints to the use of Xpert at the point-of-care. Xpert remains a relatively costly test, and clear demonstration of cost-effectiveness will be needed to support efforts to scale up testing in high burden countries.
Keywords: Xpert MTB/RIF